2021
DOI: 10.1111/jog.15092
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of brachial artery flow‐mediated dilatation, uterine artery Doppler, and umbilical artery Doppler measurements in obese and normal pregnant women

Abstract: Objective In this study, we aimed to compare vascular function at trimesters 1, 2, and 3 between obese and normal pregnant women through brachial artery flow‐mediated dilatation (FMD), uterine artery Doppler, and umbilical artery Doppler measurements. Methods Pregnant women between the ages of 18 and 40 who presented to our clinic were included. Brachial artery FMD, uterine and umbilical artery Doppler, and clinical parameters of 40 obese pregnant women from each trimester between 11 and 14 weeks, 24 and 28 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In our study, no difference was observed in UA Doppler values in obese pregnant women. In the study by Aksin et al, they observed that there was no difference between the UA Dopplers between obese and healthy pregnant women at 37-40 weeks of gestation and that there was a decrease in UA Dopplers at 24-28 weeks of gestation in obese pregnant women [20]. Sarno et al also emphasized that UA PI is associated with BMI in obese pregnant women.…”
Section: Parametersmentioning
confidence: 96%
“…In our study, no difference was observed in UA Doppler values in obese pregnant women. In the study by Aksin et al, they observed that there was no difference between the UA Dopplers between obese and healthy pregnant women at 37-40 weeks of gestation and that there was a decrease in UA Dopplers at 24-28 weeks of gestation in obese pregnant women [20]. Sarno et al also emphasized that UA PI is associated with BMI in obese pregnant women.…”
Section: Parametersmentioning
confidence: 96%